Performance Evaluation of PID Control for Distance Maintenance in Wall-Following Robots Navigating Dynamic Trajectories - Syaiful Mansur; Muhammad Ridwan Al Hafiz; Aknisa Alqibetia Sari; Ridho Akmal Sembiring (PT. GWEX NET PUBLISHER, 2026)
Autonomous navigation in wall-following robots plays a crucial role in maintaining movement stability within environments characterized by diverse path geometries. Conventional control methods often encounter oscillations and increased collision risks, particularly on dynamic trajectories. This study evaluates the performance of Proportional-Integral-Derivative (PID) control in maintaining a robot's navigation distance relative to a fixed 10 cm setpoint. The system was developed utilizing an Arduino Mega 2560 microcontroller and HC-SR04 ultrasonic sensors for distance feedback. PID parameters were determined using the Ziegler-Nichols tuning method, yielding optimal values of K_p=2, K_i=0.5, and K_d=1. Testing was conducted on both linear paths and dynamic trajectories consisting of 90° turns. The results demonstrate that on linear paths, the system successfully maintains the target distance with high precision, achieving deviations ranging from ±0.56 cm to ±1.13 cm with zero collisions. In contrast, a significant performance trade-off was observed on dynamic trajectories, where a spike in transient error led to an average distance shift to 11.88 cm and 1–2 collisions per trial. These findings highlight that while PID control is highly effective under stable linear conditions, it possesses inherent limitations in responding to rapid geometric changes and mechanical inertia. Consequently, further development, such as adaptive control logic or high-sampling-rate sensing, is required to enhance system robustness on dynamic trajectories.